Enhancement School Competitiveness Through A Literacy Culture Based on Local Wisdom - Aam Amaliyah; Hasan Baharun; Farisa Rahman; Siti Maryam (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
Increasing school competitiveness through literacy activities needs serious attention from all parties so that educational institutions can survive and attract the attention of the community. This study aims to analyze the introduction of local wisdom-based literacy culture in early childhood to strengthen children's knowledge of local culture, increasing school competitiveness against surrounding institutions. It was conducted at one of the early childhood education institutions in the Probolinggo Regency for this study. The qualitative case study method was employed in this investigation. In this study, researchers made direct observations and documented learning activities at the institution under examination. Several interviews were conducted with school administrators and teachers. As a result of learning analysis, learning system design, and evaluation, the findings revealed that introducing literacy culture based on local wisdom in early childhood effectively strengthened children's knowledge of local culture, particularly in rural areas. This study implies that teachers must have innovation and creativity in managing learning related to local culture to give enthusiasm to students in learning literacy based on local wisdom and be able to provide more trust to the community